Prehistoric and Early Medieval Fortified Settlements and High Medieval Castles on the Bohemian-Bavarian Borderland: Means of War, Power, or Symbols of Strength?/ - Hložek, Josef; Menšík, Petr; Ławrynowicz, Olgierd (Before the Battle, 2023)
The paper discusses the phenomenon of the persistence of the military, political, and social function of the present-day Bohemian-Bavarian borderland, shaped by the mountain ranges of the Bohemian Forest and the Šumava. The authors have traced the development of settlement patterns in prehistory, the Middle Ages, and the modern period, extending their studies to cover also to recent times. The discussed area constituted a barrier that limited cultural influences from both sides, which is reflected in the discovered relics of material culture. The paper also discusses, using numerous examples, the symbolic role of strongholds and castles located on mountain peaks, which came down to demonstrating the presence of power over the surrounding territory. The Bohemian-Bavarian frontier can also be seen as a peculiar landscape of conflict, which through its morphological characteristics imposed a timeless borderland form of political, military and social organisation.